Exploring Challenges of Inclusive Education in Nepal: From Policy and Practice Landscape - Baraily, Khagendra; Sherpa, Dawa (Medha: A Multidisciplinary Journal, 2025)
In Nepal, both integrated and special schools provide education to children with disabilities, supported by the government, donor agencies, or private funding. Inclusive education efforts and initiatives started as per the government's ratification of a universal declaration. However, including children with disability in the general class seems challenging. Regarding these issues, this study aims to explore the challenges that children with disability face in general classes with the existing support and ways out the coping strategies for smooth assimilation. Interpretative phenomenological research designs have been employed to explore the insights and perspectives of students on assimilation in general classes. The four students with disability from integrated schools representing children with visual impairment and children with deaf were purposively selected and interviewed through semi-structured interview guidelines in a natural setting. The study explored significant challenges such as the lack of disabled-friendly physical facilities, the domination of traditional methods, the presence of an untrained teacher, the lack of an expanded core curriculum, the lack of peer support, and poor psychological attachment. The exploration of challenges assists policymakers and educators in setting up strategies for effective inclusion in school education and the community. The extreme mitigation of challenges promotes an inclusive atmosphere in regular classrooms.